Hambatan Komunikasi Politik Antar Partai di Parlemen - Agus Tohamba; Ulfah Attamimi (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
This study examines the communication barriers that occur in the Setgab, led by the Democratic Party with its coalition partners in Parliament, regarding the Government's Policy which proposes an increase in fuel prices in the 2012 Revised State Budget Bill. This study is based on the theorization of social construction theory, symbolic interaction theory, and dramaturgical theory. Researchers choose the constructivist paradigm as a perspective in seeing the object of research, and use a qualitative approach to obtain in-depth findings, through case study methods to find specifics. Primary data was obtained through in-depth interviews with key informants and direct observation by observing the course of every meeting to discuss government proposals at Commission VII DPR, Banggar DPR and DPR Plenary Sessions. The data were analyzed qualitatively using domain and taxonomy analysis. The results of the study indicate that there are communication barriers that cause: communication that does not reach the bottom, weak control and commitment in the Setgab, differences in interests, mass media and public opinion, becoming a stage for performances, and freedom of opinion that hinders communication. Meanwhile, why Setgab does not run ideally is because the position of Setgab is not legally binding on coalition partners in Parliament. The conclusion clearly shows that there is a communication situation that does not work effectively because of communication barriers. Therefore, there needs to be a political breakthrough that legally binds every political party when pledging a coalition in Parliament, in order to improve effective political communication in the next period.